The Implementation of Humanistic Learning at Darul Aman Islamic High School in Aceh Besar - Sulaiman Sulaiman (Ulumuna, 2017)
This article focuses on humanistic learning at an Islamic private school in Aceh. It uses qualitative descriptive method and takes seven subjects as the sample of the data. It shows that the humanistic learning in Darul Aman Private Madrasah Aliyah of Aceh Besar was implemented through three mechanisms. First, creating a humanist class situation, both physical and non-physical environment (socio-emotional), through a democratic approach. Second, employing a cooperative learning model as the basis of humanistic learning. Third, adopting an effective communication model in creating humanistic learning interactions. This involves cycle-models of communication and interaction of learning: one direction interaction (teacher-student), teacher-learners-learners (their feedback for teachers; students learn from each other) and multi-interaction of the teacher-learner, learner-teacher, learners-learners (interaction in many directions). The implementation of humanistic learning at Darul Aman Private Madrasah Aliyah of Aceh Besar had a problem in the form of limited instructional media resources. Nevertheless, the overall learning process was humanist. DOI: http://dx.doi.org/10.20414/ujis.v21i1.1161